The Anglo-Egyptian Sudan: a compendium prepared by officers of the Sudan government, Vol. 1 (of 2) - Sudan. Wizarat al-Naql wa-al-Muwasalat; Gleichen, Edward, Lord, 1863-1937 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Anglo-Egyptian Sudan: A Compendium Prepared by Officers of the Sudan Government" edited by Lieut.-Colonel Count Gleichen is a comprehensive historical account written in the early 20th century. This work serves as an extensive guide on the geographical, administrative, and historical aspects of the Anglo-Egyptian Sudan around 1905, showcasing the region's resources, governance, and development since the late 19th century. The compilation aims to provide useful information for both government officials and the general public interested in the Sudan's progress and future. At the start of the compendium, the preface outlines its purpose as a detailed description of the Sudan, including revisions of earlier handbooks and new insights into the country's resources and administration. Various officials and experts contributed chapters that discuss the geographical boundaries, population distribution, and the administrative framework under British and Egyptian rule. The introduction emphasizes Sudan's vast area, capital city of Khartoum, and the structures in place for governance and resource management, all pivotal for understanding the socio-political landscape at that time. (This is an automatically generated summary.)
Vol. 1: Geographical, descriptive and historical.
Release date is 2024-10-15
Galo Flordelis (This file was produced from images generously made available by The Internet Archive/University of Pretoria)
Keywords: Sudan -- Description and travel; Sudan -- History